Synthesis and Characterization of 3-Coumaryl-4-Aroyl-5-Aryl Pryazolines - Thakre, N.R.; Jamode, V.S. (Asian Journal of Chemistry, 2010)
New 3-(4-methyl-7-hydroxy coumaryl)-4-(4'-methoxy benzoyl)-5-aryl pyrazolines (4a-i) have been synthesised by the action of hydrazinelisoniazid/semicarbazide, with 2-aryl-3-[4-methoxy benzoyl)- 5,6-[4-methyl-7,8-coumaryl] flavanones (3a-c) in pyridine medium.